Finding the tomb of Suleiman the Magnificent in Szigetvár, Hungary: historical, geophysical and archeological investigations - Pap, Norbert; Kitanics, Maté; Gyenizse, Péter; Hancz, Erika; Bognár, Zita; Tóth, Tamás; Hámori, Zoltán (DIE ERDE – Journal of the Geographical Society of Berlin, 2015)
Exploration in search of the tomb of Sultan Suleiman I and the buildings around it in the vicinity of Szigetvár, Baranya county, southern Hungary, has been going on for some one hundred years and on a number of sites (on the banks of Almás stream, at St. Mary’s Church in Turbék). On the basis of newly discovered documents and map representations, the authors have carried out a reinterpretation of earlier known sources and have abstracted from these information appropriate for a renewed geographical identification of the site of the tomb. The results have been construed in a reconstructed end-17th-century landscape using geoinformation methods. Identification of the Ottoman settlement at Turbék, which can be associated with the construction of the Sultan’s türbe (tomb), was made possible through the collection of finds on the surface of the archaeological site at the Turbék vineyard, the increased intensity of finds and through geophysical examination. The little town was a unique settlement in occupied Hungary, standing between 1574 and 1692 as a symbol of the Islamic conquest of the region